2021
DOI: 10.1108/er-05-2020-0242
|View full text |Cite
|
Sign up to set email alerts
|

Job stress and employee outcomes: employment practices in a charity

Abstract: PurposeThe study intends to examine employee relations with a changing workforce resulting from the business-like transformation in the charity sector. The authors investigated sector-specific employment practices that can alleviate job stress (as a given and which has been made worse by the transformation). Developed from the intrinsic and extrinsic motivation framework, the findings can inform human resource management practices in its new efficiency-seeking business model.Design/methodology/approachThe auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The high-stress level at the workplace leads to psychological and physical problems among employees [79]. Notably, the negative relationship between job stress and satisfaction determines employees' perception of meaningful work and engagement in decision-making [21]. Generally, the current research has various academic implications.…”
Section: Academic Implicationmentioning
confidence: 96%
See 1 more Smart Citation
“…The high-stress level at the workplace leads to psychological and physical problems among employees [79]. Notably, the negative relationship between job stress and satisfaction determines employees' perception of meaningful work and engagement in decision-making [21]. Generally, the current research has various academic implications.…”
Section: Academic Implicationmentioning
confidence: 96%
“…Worker's stress has emerged as a common occupational disease, which has affected employees psychologically and physically; thus, affecting their performance [20]. Besides, job stress affects employee outcomes and satisfaction [21]. Job stress occurs due to many factors, such as workload, lack of incentives, and motivation [22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, psychological stress from work and family relations may distract employees and reduce their enthusiasm for work (Schmitt et al , 2016). Existing studies have suggested that psychological distress is positively related to workplace injuries and interpersonal conflict (Turner et al , 2014; Grubbs and Exline, 2016) and is negatively associated with job satisfaction and affective commitment (Wang and Seifert, 2021).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%